Large room-temperature ferromagnetism in ordered porous In2O3 films. Issue 7 (1st April 2022) - Dong, Meiyu; Zhang, Lu; Liu, Lihu; Xu, Qin; Sun, Huiyuan
Abstract: In this paper, ordered porous In2 O3 films were prepared on ordered porous Al2 O3 thin films by magnetron sputtering. The film shows large room-temperature ferromagnetism of 18.78 emu/cm 3, and the saturation magnetization is more than ten times larger than in the dense In2 O3 film. Moreover, the magnetic anisotropy of the ordered porous In2 O3 film was observed, and the saturation magnetization in the direction perpendicular to the film surface is much greater than in the direction parallel to the film surface. In addition, by investigating the room-temperature ferromagnetism and photoluminescence properties of the film under different environments, the room-temperature ferromagnetism of ordered porous In2 O3 films is most affected by the oxygen vacancies. The research in this paper provides a solid basis for the development of spintronic devices.